Will indigenous plant knowledge survive? Documenting ethnobotany among Mongolia's nomadic communities in the Gobi desert - McCarthy, C.; Phillips, S.; Nergui, K.; Adiya, T.; Yadamsuren, A.; Sternberg, T.; Hoshino, B.; Nasanbat, B.; Enkhjargal, E. (Journal of Ethnobiology, 2025)
This study investigates the current state of plant knowledge and use among nomadic communities in Mongolia's Gobi Desert, where rapid socioeconomic and environmental changes threaten traditional practices. Through a comprehensive survey of 50 participants aged 12–65 across four aimags, we documented the recognition, utilization, and cultural significance of 17 key plant species. High recognition rates were found for Haloxylon ammodendron, Agriophyllum pungens, and Rheum nanum, with medicinal use being the most frequently reported category. Environmental changes, particularly reduced water availability and habitat disruption due to mining activities, have significantly affected plant abundance and use. Importantly, while most respondents demonstrated knowledge of specific land management practices, including seasonal migration and protecting water sources, some were unfamiliar with formal conservation techniques. Concerns about the decline of plant knowledge among younger generations were prevalent among participants. The expansion of mining activities, affecting a substantial portion of the study area, emerged as a primary concern. These findings underscore the cultural, economic, and medicinal importance of specific plant species in the region. The study highlights the urgent need to preserve traditional ecological knowledge in the face of rapid environmental and economic changes. This research contributes to understanding the current ethnobotanical landscape in the Gobi Desert and offers insights for developing strategies to support biocultural diversity conservation amidst increasing challenges to nomadic livelihoods and traditional practices.